Polypropylene-based resin composition and method for producing the same, film molded article, packaging in contact with food, container in contact with food, and retort pouch
Patent Information
- Application Number
- CN202280043302.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-06-25
- Filing Date
- 2022-06-24
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2042-06-24
AI Technical Summary
Existing polypropylene-based resin compositions are not suitable for preparing film molded products that meet FDA testing standards, especially in food contact retort pouch applications, as they cannot simultaneously meet the requirements for rigidity, impact resistance, weldability, and low permeability.
A polypropylene-based resin composition consisting of a specific ratio of propylene polymer and ethylene/α-olefin copolymer is polymerized under certain temperature and pressure using a catalyst composed of magnesium, titanium, halogens and phthalate compounds to prepare a film molded product with excellent mechanical and chemical properties.
This invention achieves low permeability in FDA testing of polypropylene-based resin compositions, and possesses an excellent balance of rigidity, low-temperature impact strength, and weldability. It is suitable for food contact packaging, containers, and retort pouches, and is widely used in packaging, home appliances, electrical and electronic components, automotive parts, and other fields.
Smart Images

Figure BDA0004612191340000171 
Figure BDA0004612191340000201 
Figure HDA0004612191350000011
Abstract
Description
Technical Field
[0001] This invention relates to a polypropylene-based resin composition, a method for preparing the same, a film-molded article, food-contact packaging, food-contact containers, and retort pouches. This application claims priority to Japanese Patent Application No. 2021-105706, filed on June 25, 2021, the contents of which are incorporated herein by reference. Background Technology
[0002] Polypropylene has excellent physical properties, such as impact resistance, rigidity, transparency, chemical resistance and heat resistance, and is therefore widely used in a variety of applications.
[0003] For example, Patent Document 1 discloses a polypropylene-based resin composition suitable for obtaining injection-molded articles with an excellent balance of rigidity and impact resistance as well as a good appearance.
[0004] Existing technical documents
[0005] Patent Document 1: Japanese Unexamined Patent Application Publication No. 2019-189818. Summary of the Invention
[0006] The problem to be solved by the present invention
[0007] Applications of polypropylene-based resin compositions in film molding include, for example, packaging materials such as retort pouches for food. These applications require not only mechanical properties, such as rigidity and impact resistance, but also chemical properties, such as reduced elution of components upon contact with oils or solvents. In particular, for applications in food-contact retort pouches, it is required that the components of the film molding hardly leach into the food. For example, testing standards established by the U.S. Food and Drug Administration (FDA) stipulate that the elution (extraction) amount in n-hexane should be 2.6 μg or less. Furthermore, in some cases, retort pouch applications require high heat-sealing properties (weldability), high impact resistance at low temperatures, and excellent appearance.
[0008] The polypropylene-based resin composition disclosed in Patent Document 1 has a high MFR, and therefore is not suitable for obtaining molded articles. Furthermore, it does not take into account FDA testing standards, nor the various mechanical and chemical properties required for molded articles.
[0009] This invention provides a polypropylene-based resin composition, a method for preparing the same, and a molded article thereof. This polypropylene-based resin composition allows for the production of molded articles that exhibit a small amount of elution into n-hexane in FDA testing and possess an excellent balance of rigidity, low-temperature impact strength, weldability, and resistance to flexural whitening (anti-whitening). This invention also provides food contact packaging, a food contact container, and a retort pouch.
[0010] Problems to be solved
[0011] The present invention has the following aspects.
[0012] [1] A polypropylene-based resin composition comprising
[0013] A polypropylene-based resin (A) comprising a continuous phase composed of a propylene polymer (a1) and a rubber phase composed of a copolymer of ethylene and an α-olefin having 3 to 10 carbon atoms (a2), and
[0014] Ethylene / α-olefin copolymer (B), which is a copolymer of ethylene and an α-olefin having 3 to 10 carbon atoms as an optional component.
[0015] The content of the polypropylene-based resin (A) is 90% by weight or more and less than 100% by weight relative to the total weight of the polypropylene-based resin composition.
[0016] The content of the ethylene / α-olefin copolymer (B) is 0 to 10% by weight relative to the total weight of (A) and (B).
[0017] The MFR of the polypropylene-based resin composition at 230°C and a load of 2.16 kg is 0.5 to 4.0 g / 10 minutes.
[0018] The weight-average molecular weight M of the propylene polymer (a1) w Number-average molecular weight M n The ratio (M) w / M n Less than 7,
[0019] The content of ethylene-derived units in the propylene polymer (a1) is 0.5% by weight or less relative to the total weight of the propylene polymer (a1).
[0020] The content of the copolymer (a2) is 30% to 43% by weight relative to the total weight of the polypropylene-based resin (A).
[0021] The content of ethylene-derived units in the copolymer (a2) is 25% to 40% by weight relative to the total weight of the copolymer (a2).
[0022] The xylene-soluble portion of the polypropylene-based resin (A) has an intrinsic viscosity of 2.5 to 3.5 dl / g in tetrahydronaphthalene at 135°C, and
[0023] The MFR of the polypropylene-based resin (A) at a temperature of 230°C and a load of 2.16 kg is 0.5 to 4.0 g / 10 min.
[0024] [2] According to the polypropylene-based resin composition of [1], wherein the propylene polymer (a1) and the copolymer (a2) are mixed by polymerization, and the polypropylene-based resin (A) is a polymeric mixture prepared by using a catalyst containing the following components (a) to (c);
[0025] (a) A solid catalyst containing magnesium, titanium, halogens, and phthalate-based compounds as electron donors.
[0026] (b) Organoaluminum compounds, and
[0027] (c) Organosilicon compounds that act as external electron donors.
[0028] [3] A method for preparing a polypropylene-based resin composition according to [1] or [2], comprising the steps of: polymerizing an ethylene monomer and an α-olefin monomer having 3 to 10 carbon atoms using a catalyst containing the following components (a) to (c) in the presence of the propylene polymer (a1) to obtain the polypropylene-based resin (A).
[0029] (a) A solid catalyst containing magnesium, titanium, halogens, and phthalate-based compounds as electron donors as essential components.
[0030] (b) Organoaluminum compounds, and
[0031] (c) Organosilicon compounds that act as external electron donors.
[0032] [4] A film-molded article formed from a polypropylene-based resin composition according to [1] or [2].
[0033] [5] The film-molded article according to [4] is used as packaging or container in contact with food.
[0034] [6] The film-molded article according to [4] or [5] is used as at least a portion of a retort pouch.
[0035] [7] A food-contact packaging formed from a film-molded article according to [4].
[0036] [8] A container for contact with food, formed from a film-molded article according to [4].
[0037] [9] A retort bag formed from a film-molded article according to [4].
[0038] Effects of the present invention
[0039] By using the polypropylene-based resin composition of the present invention, film-molded articles that meet FDA testing standards and are suitable for food contact retort pouches can be obtained. Furthermore, the film-molded articles of the present invention have an excellent balance of rigidity, low-temperature impact strength, weldability, and anti-whitening properties, thus making them suitable not only for food contact applications but also for packaging or containers for various items.
[0040] Besides packaging applications, it can be used for any purpose, including, for example, groceries, daily necessities, household appliance parts, electrical and electronic parts, automotive parts, housing parts, toy parts, furniture parts, building material parts, packaging parts, industrial materials, logistics materials, agricultural materials, etc. Attached Figure Description
[0041] [ Figure 1 ] Figure 1 A cross-sectional view of the heat-sealed membrane sample is shown in the figure.
[0042] [ Figure 2 ] Figure 2 This is a perspective view of an exemplary film molded article of the present invention.
[0043] [ Figure 3 ] Figure 3 This is a perspective view of an exemplary food container of the present invention.
[0044] [ Figure 4 ] Figure 4 This is a front view of an exemplary retort bag for food according to the present invention. Detailed Implementation
[0045] <Polypropylene-based resin composition>
[0046] The polypropylene-based resin composition of the present invention comprises a polypropylene-based resin (A) (hereinafter also referred to as component (A)), which includes a continuous phase composed of a propylene polymer (hereinafter also referred to as component (a1)) and a rubber phase composed of a copolymer of ethylene and an α-olefin having 3 to 10 carbon atoms (hereinafter also referred to as component (a2)).
[0047] In addition, as an optional component, it may include or exclude an ethylene / α-olefin copolymer (B) (hereinafter also referred to as component (B)), which is a copolymer of ethylene and an α-olefin having 3 to 10 carbon atoms.
[0048] The content of polypropylene-based resin (A) is between 90% by weight or more and less than 100% by weight relative to the total weight of the polypropylene-based resin composition, with the lower limit preferably being 90% by weight or more, more preferably 95% by weight or more, and even more preferably 99% by weight or more.
[0049] If it is equal to or greater than the lower limit of the above range, the above-mentioned effects of the present invention can be fully obtained.
[0050] If it is less than the upper limit of the above range, there is space to accommodate component (B) or other components.
[0051] The content of ethylene / α-olefin copolymer (B) is 0 to 10% by weight relative to the total weight of component (A) and component (B), and the upper limit is preferably 10% by weight or less, more preferably 5% by weight or less, and even more preferably 0% by weight.
[0052] When the content exceeds 0% by weight (which is the lower limit of the above range), the impact resistance of the molded article increases. However, from the viewpoint of maintaining rigidity, a content of 0% by weight is preferred.
[0053] When the content is 10% by weight or less (which is the upper limit of the above range), the amount eluted into n-hexane in FDA testing of the film molded product can be sufficiently reduced.
[0054] The MFR of the polypropylene-based resin composition at a temperature of 230°C and a load of 2.16 kg is 0.5 to 4.0 g / 10 min, with the lower limit preferably being 1.0 g / 10 min or more, and more preferably 1.5 g / 10 min or more. Furthermore, the upper limit is preferably 3.5 g / 10 min or less, more preferably 3.0 g / 10 min or less, and even more preferably 2.5 g / 10 min or less. In other words, examples include ranges of 0.5 to 3.5 g / 10 minutes, 0.5 to 3.0 g / 10 minutes, 0.5 to 2.5 g / 10 minutes, 1.0 to 4.0 g / 10 minutes, 1.0 to 3.5 g / 10 minutes, 1.0 to 3.0 g / 10 minutes, 1.0 to 2.5 g / 10 minutes, 1.5 to 4.0 g / 10 minutes, 1.5 to 3.5 g / 10 minutes, 1.5 to 3.0 g / 10 minutes, and 1.5 to 2.5 g / 10 minutes. Here, MFR is a value measured by the measurement method described below.
[0055] When it is equal to or greater than the lower limit of the above range, the film formability is excellent.
[0056] When it is equal to or less than the upper limit of the above range, the mechanical properties of the molded product can be improved.
[0057] [Polypropylene-based resin (A)]
[0058] The polypropylene-based resin (A) included in the polypropylene-based resin composition of the present invention is an example of an impact-resistant polypropylene polymer specified in JIS K6921-1, and is composed of two or more phases, including a continuous phase of a propylene polymer (component (a1)) and a rubber phase of an ethylene / α-olefin copolymer (component (a2)) existing as a dispersed phase in the continuous phase.
[0059] The polypropylene-based resin (A) can be a mixed resin in which components (a1) and (a2) are mixed during polymerization, or a mixed resin in which separately obtained components (a1) and (a2) are mixed by melt kneading. It is preferred to mix components (a1) and (a2) (polymerization mixture) during polymerization because this allows for an excellent balance between rigidity, low-temperature impact resistance, and tensile properties (hereinafter also referred to as "mechanical-physical property balance") at a lower cost.
[0060] In the polymerization mixture, components (a1) and (a2) can be mixed with each other at the submicron level, and the polypropylene-based resin composition based on the polymerization mixture exhibits an excellent balance of mechanical and physical properties.
[0061] On the other hand, if similar homogeneous mixing and a superior balance of mechanical and physical properties are achieved using a simple mechanical mixture obtained by melt kneading of separately obtained components (a1) and (a2), the manufacturing cost increases due to the need for separate processes such as storage, transportation, measurement, mixing, melting, and kneading. This is also disadvantageous from an energy cost perspective.
[0062] It is speculated that the different physical properties exhibited by polymeric and mechanical mixtures are due to the difference in the dispersion state of component (a2) within component (a1). Currently, there is no known practical method to analyze the dispersion state of component (a2) at the molecular level, including its interfacial state with component (a1). The method for preparing the polypropylene-based resin (A) will be described in detail later.
[0063] The intrinsic viscosity (hereinafter also referred to as "XSIV") of the xylene-soluble portion of the polypropylene-based resin (A) is 2.5 to 3.5 dl / g, with the lower limit preferably being 2.7 dl / g or higher. Furthermore, the upper limit is preferably 3.3 dl / g or lower. That is, examples include ranges of 2.5 to 3.3 dl / g, 2.7 to 3.5 dl / g, and 2.7 to 3.3 dl / g. Here, XSIV is a value measured by a method described later.
[0064] When it is equal to or greater than the lower limit of the above range, the sealing strength of the membrane molded product increases.
[0065] When it is equal to or less than the upper limit of the above range, the FE generated in the film molded article can be reduced and undesirable appearance (the appearance of spots) can be suppressed.
[0066] The weight-average molecular weight M is an index of the molecular weight distribution of the propylene polymer (component (a1)) that constitutes the polypropylene-based resin (A). w Number-average molecular weight M n The ratio (M) w / M n The value is less than 7. When it is less than 7, the low-temperature impact resistance and anti-whitening properties of the film-molded products increase.
[0067] There is no particular limitation on the lower limit of the above ratio, and, for example, 3 or above can be mentioned as a guideline.
[0068] Here, the weight-average molecular weight M of the propylene polymer is... w Number-average molecular weight M n The value is measured using the following method.
[0069] The content of ethylene-derived units (hereinafter also referred to as "C2") in the propylene polymer (component (a1)) constituting the polypropylene-based resin (A) is 0.5% by weight or less, preferably 0.3% by weight or less, relative to the total weight of the propylene polymer.
[0070] When C2 is equal to or less than the upper limit, the rigidity of the molded product increases.
[0071] There is no particular restriction on the lower limit of C2, and it can be 0% by weight.
[0072] In other words, the propylene polymer can be a polypropylene homopolymer consisting solely of propylene-derived units, or a copolymer consisting of 99.5% by weight or more but less than 100% by weight of propylene-derived units and greater than 0% by weight but less than 0.5% by weight of ethylene-derived units. C2 through 13 Measured by C-NMR method.
[0073] The ethylene / α-olefin copolymer (component (a2)) constituting the polypropylene-based resin (A) is a copolymer having ethylene-derived units and α-olefin-derived units having 3 to 10 carbon atoms.
[0074] The content of ethylene-derived units in component (a2) is 25 to 40% by weight relative to the total weight of component (a2), with the lower limit preferably being 28% by weight or more. Furthermore, the upper limit is preferably 35% by weight or less, more preferably 33% by weight or less. That is, examples include ranges of 25 to 35% by weight, 25 to 33% by weight, 28 to 40% by weight, 28 to 35% by weight, and 28 to 33% by weight.
[0075] When it is equal to or greater than the lower limit of the above range, the low-temperature impact resistance of the film molded product increases.
[0076] When it is equal to or less than the upper limit of the above range, the amount eluted into n-hexane in FDA testing can be sufficiently reduced for molded membranes. Furthermore, it can improve resistance to whitening.
[0077] The content of ethylene-derived units in component (a2) is determined by... 13 Measured by C-NMR method.
[0078] The content of the ethylene / α-olefin copolymer (component (a2)) relative to the total weight of the polypropylene-based resin (A) is 30 to 43% by weight, with the lower limit preferably being 31% by weight or more. Furthermore, the upper limit is preferably 38% by weight or less, more preferably 35% by weight or less. That is, examples include ranges of 30 to 38% by weight, 30 to 35% by weight, 31 to 43% by weight, 31 to 38% by weight, and 31 to 35% by weight.
[0079] When it is equal to or greater than the lower limit of the above range, the low-temperature impact resistance of the film molded product increases.
[0080] If it is equal to or less than the upper limit of the above range, the risk of clogging the flow path on the production equipment due to the deterioration of powder flowability during the production of polypropylene-based resin (A) can be reduced, enabling stable and continuous production of polypropylene-based resin (A).
[0081] Examples of α-olefins constituting ethylene / α-olefin copolymers (component (a2)) include propylene (1-propylene), 1-butene, 1-pentene, 1-hexene, and 1-octene.
[0082] Specific examples of component (a2) include ethylene / propylene copolymers, ethylene / butene copolymers, ethylene / pentene copolymers, ethylene / hexene copolymers, ethylene / octene copolymers, etc.
[0083] Among them, considering the improvement of the productivity of polypropylene-based resin (A), ethylene / propylene copolymer is preferred.
[0084] The MFR of the polypropylene-based resin (A) at a temperature of 230°C and a load of 2.16 kg is 0.5 to 4.0 g / 10 min, with the lower limit preferably being 1.0 g / 10 min or more, and even more preferably 1.5 g / 10 min or more. Furthermore, the upper limit is preferably 3.5 g / 10 min or less, more preferably 3.0 g / 10 min or less, and even more preferably 2.5 g / 10 min or less. In other words, examples include ranges of 0.5 to 3.5 g / 10 min, 0.5 to 3.0 g / 10 min, 0.5 to 2.5 g / 10 min, 1.0 to 4.0 g / 10 min, 1.0 to 3.5 g / 10 min, 1.0 to 3.0 g / 10 min, and 1.0 to 2.5 g / 10 min. Here, the MFR is a value measured by the measurement method described later.
[0085] When it is equal to or greater than the lower limit of the above range, the film formability is excellent.
[0086] When it is equal to or less than the upper limit of the above range, it can improve the sealing strength of the film molded product and improve its low-temperature impact resistance.
[0087] [Ethylene / α-olefin copolymer (B)]
[0088] Ethylene / α-olefin copolymer (B) is a copolymer of ethylene and an α-olefin having 3 to 10 carbon atoms. Examples of α-olefins include propylene (1-propylene), 1-butene, 1-pentene, 1-hexene, and 1-octene.
[0089] Specific examples of ethylene / α-olefin copolymers (B) include ethylene / butene copolymers, ethylene / pentene copolymers, ethylene / hexene copolymers, ethylene / octene copolymers, etc.
[0090] Among these considerations, the availability and economic efficiency of the raw materials are preferred, and ethylene / butene copolymer or ethylene / octene copolymer is preferred.
[0091] The MFR of the ethylene / α-olefin copolymer (B) at a temperature of 190°C and a load of 2.16 kg is preferably 0.5 to 20 g / 10 min. Here, the MFR is a value measured by the measurement method described later.
[0092] When it is equal to or greater than the lower limit of the above range, the fluidity of the polypropylene-based resin composition increases.
[0093] When it is equal to or less than the upper limit of the above range, adhesion in the polypropylene-based resin composition can be suppressed, and the continuous production rate of the composition can be improved. Furthermore, the low-temperature impact resistance and tensile properties of the molded film are improved.
[0094] [Other components]
[0095] The polypropylene-based resin composition of the present invention may include polymers other than polypropylene-based resin (A) and ethylene / α-olefin copolymer (B) (other polymers) and / or additives as optional components, the scope of which does not impair the effects of the present invention.
[0096] Examples of other polymers include propylene polymers other than polypropylene-based resins (A), ethylene polymers other than ethylene / α-olefin copolymers (B), elastomers, plasmons, terpolymers, and recycled polymers. One or more types of other polymers may be included. The content of other polymers may be adjusted as needed for the application, but their content relative to the total weight of the polypropylene-based resin composition shall be 10% by weight or less. For example, it may be 8% by weight or less, 6% by weight or less, 4% by weight or less, 2% by weight or less, or 1% by weight or less.
[0097] Examples of additives include, for instance, antioxidants, neutralizers, nucleating agents, weathering agents, pigments (organic or inorganic), internal and external lubricants, anti-blocking agents, antistatic agents, chlorine absorbers, heat stabilizers, light stabilizers, UV absorbers, slip agents, anti-fogging agents, flame retardants, dispersants, copper damage inhibitors, plasticizers, foaming agents, defoamers, crosslinking agents, peroxides, oil fillers, etc. These additives can be used alone or in combination of two or more types. The content can be a known amount.
[0098] <Preparation Method of Polypropylene-based Resin Composition>
[0099] Examples of methods for preparing the polypropylene-based resin compositions of the present invention include a method in which a polypropylene-based resin (A) and an optional ethylene / α-olefin copolymer (B) are mixed and then melt-kneaded.
[0100] Examples of mixing methods include dry mixing using mixers such as Henschel mixers, drum mixers, and ribbon mixers.
[0101] Examples of melt-kneading methods include mixing using methods such as single-screw extruders, twin-screw extruders, Banbury mixers, kneaders, and roller mills during melting. The melt temperature during melt-kneading is preferably 160 to 350°C, more preferably 170 to 260°C. Further granulation can be performed after melt-kneading.
[0102] [Preparation method of polypropylene-based resin (A)]
[0103] The polypropylene-based resin (A) is obtained by mixing a propylene polymer (component (a1)) and an ethylene / α-olefin copolymer (component (a2)) during polymerization. Alternatively, components (a1) and (a2) prepared separately can be mixed by melt kneading.
[0104] Preferred polypropylene-based resin (A) is a polymeric mixture in which components (a1) and (a2) are mixed during polymerization.
[0105] This polymerization mixture is obtained by polymerizing ethylene monomers and α-olefin monomers in the presence of component (a1). According to this method, productivity is improved, and the dispersion of component (a2) in component (a1) is increased, resulting in an improved balance of the mechanical and physical properties of the film molded articles obtained using this method.
[0106] The following text describes the use of propylene monomers as α-olefin monomers, which can also be used in production when other α-olefin monomers are used.
[0107] Multi-stage polymerization is commonly used as a method for preparing polymeric mixtures. For example, a polymeric mixture may be obtained as follows: propylene monomer and (if necessary) ethylene monomer are polymerized in a first-stage polymerization reactor of a polymerization apparatus equipped with two-stage polymerization reactors to obtain a propylene polymer, and the resulting polypropylene polymer is supplied to a second-stage polymerization reactor, where ethylene monomer and propylene monomer are polymerized.
[0108] The polymerization conditions can be similar to known polymerization conditions. For example, first-order polymerization conditions include slurry polymerization methods in which propylene is in the liquid phase and monomer density and yield are high. As second-order polymerization conditions, gas-phase polymerization methods that generally allow for the easy preparation of copolymers with high solubility in propylene can be mentioned.
[0109] The polymerization temperature is preferably 50 to 90°C, more preferably 60 to 90°C, and even more preferably 70 to 90°C. When the polymerization temperature is equal to or higher than the lower limit of the above range, the yield and stereoregularity of the resulting polypropylene are superior.
[0110] When carried out in the liquid phase, the polymerization pressure is preferably 25 to 60 bar (2.5 to 6.0 MPa), more preferably 33 to 45 bar (3.3 to 4.5 MPa). When carried out in the gas phase, the pressure is preferably 5 to 30 bar (0.5 to 3.0 MPa), more preferably 8 to 30 bar (0.8 to 3.0 MPa).
[0111] Polymerization (polymerization of propylene monomers, polymerization of ethylene monomers, etc.) is typically carried out using a catalyst. During polymerization, hydrogen may be added if necessary to adjust the molecular weight. By adjusting the molecular weight of the propylene polymer or ethylene / propylene copolymer, the molecular weight ratio (MFR) of the polypropylene-based resin (A) can be adjusted, thereby adjusting the MFR of the polypropylene-based resin composition.
[0112] Prior to polymerization in the first-stage polymerization reactor, propylene can be prepolymerized to form polymer chains in the solid catalyst component, which will serve as the foothold for subsequent main polymerization. Prepolymerization is typically carried out at a temperature of 40°C or below, preferably 30°C or below, and more preferably 20°C or below.
[0113] Known olefin polymerization catalysts can be used as catalysts.
[0114] Stereotactic Ziegler-Natta catalysts are preferred as catalysts for polymerizing ethylene monomers and propylene monomers in the presence of propylene polymers, and catalysts comprising components (a), (b) and (c) (hereinafter also referred to as “catalyst (X)”) are particularly preferred.
[0115] (a) A solid catalyst containing magnesium, titanium, halogens and phthalate-based compounds as electron donors as essential components.
[0116] (b) Organoaluminum compounds.
[0117] (c) Organosilicon compounds that act as external electron donors.
[0118] Preferably, the polypropylene-based resin (A) is prepared in a method comprising the step of polymerizing ethylene monomer and α-olefin monomer (e.g., propylene monomer) in the presence of a propylene polymer using a catalyst (X) to obtain a polypropylene-based resin. By using the catalyst (X), polypropylene-based resin (A) with physical properties within the aforementioned ranges can be readily obtained.
[0119] It should be noted that the molecular weight and stereoregularity distributions of the resulting propylene polymers vary depending on the catalyst used (particularly for the electron-donating compound in (a)), and these differences affect crystallization behavior, etc., but the detailed relationship between them has not yet been revealed. To clarify this, it is necessary to analyze the molecular weight and stereoregularity distributions as molecular structures, but this is complex because components with different molecular weights and stereoregularities influence each other during crystallization, making it more difficult to explain the effects of molecular weight and stereoregularity distributions on crystallization behavior. Furthermore, since actual film molding is carried out in the fluidized state of molten resin, this phenomenon is not easily understood even using advanced analytical techniques. Therefore, in polypropylene-based resin compositions obtained using a certain catalyst, it is almost impossible to numerically or in any other way explain the differences in crystallization behavior due to molecular weight distribution or stereoregularity. The molecular weight and stereoregularity distributions change not only with the type of catalyst mentioned above, but also through thermal degradation during melting and kneading, peroxide treatment, etc.
[0120] Component (a) is prepared using, for example, titanium compounds, magnesium compounds and electron donor compounds.
[0121] The titanium compound used as component (a) is derived from the general formula: Ti(OR) g X 4-g (R is a hydrocarbon group, X is a halogen, 0≤g≤4) indicates a suitable tetravalent titanium compound.
[0122] Examples of hydrocarbon groups include methyl, ethyl, propyl, butyl, etc., and examples of halogens include Cl, Br, etc.
[0123] More specific titanium compounds include: titanium tetrahalides, such as TiCl4, TiBr4, and TiI4; and titanium trihaloalkoxy compounds, such as Ti(OCH3)Cl3, Ti(OC2H5)Cl3, and Ti(O n -C4H9)Cl3, Ti(OC2H5)Br3, Ti(O-isoC4H9)Br3; dihaloalkoxy titanium, such as Ti(OCH3)2Cl2, Ti(OC2H5)2Cl2, Ti(O n -C4H9)2Cl2, Ti(OC2H5)2Br2; monohalogenated trialkoxy titanium, such as Ti(OCH3)3Cl, Ti(OC2H5)3Cl, Ti(O n -C4H9)3Cl, Ti(OC2H5)3Br; tetraalkoxy titanium, such as Ti(OCH3)4, Ti(OC2H5)4, Ti(O n -C4H9)4. These titanium compounds can be used alone or in combination of two or more types.
[0124] Among the above-mentioned titanium compounds, halogen-containing titanium compounds are preferred, titanium tetrahalides are more preferred, and titanium tetrachloride (TiCl4) is particularly preferred.
[0125] The magnesium compounds used in component (a) include those having magnesium-carbon or magnesium-hydrogen bonds, such as dimethylmagnesium, diethylmagnesium, dipropylmagnesium, dibutylmagnesium, dipentylmagnesium, dihexylmagnesium, didecylmagnesium, ethyl magnesium chloride, propyl magnesium chloride, butyl magnesium chloride, hexyl magnesium chloride, pentyl magnesium chloride, butylethoxymagnesium, ethylbutylmagnesium, butyl hydride, etc. These magnesium compounds may also be used in the form of complexes with, for example, organoaluminum compounds, and may be in liquid or solid form. Other suitable magnesium compounds include: magnesium halides, such as magnesium chloride, magnesium bromide, magnesium iodide, and magnesium fluoride; alkoxy magnesium halides, such as methoxy magnesium chloride, ethoxy magnesium chloride, isopropoxy magnesium chloride, butoxy magnesium chloride, and octoxy magnesium chloride; allyloxy magnesium halides, such as phenoxy magnesium chloride and methylphenoxy magnesium chloride; alkoxy magnesium, such as ethoxy magnesium, isopropoxy magnesium, butoxy magnesium, n-octoxy magnesium, and 2-ethylhexyloxy magnesium; dialkoxy magnesium, such as dimethoxy magnesium, diethoxy magnesium, dipropoxy magnesium, dibutoxy magnesium, and ethoxymethoxy magnesium; and allyloxy magnesium, such as ethoxypropoxy magnesium, butoxyethoxy magnesium, phenoxy magnesium, and dimethylphenoxy magnesium. These magnesium compounds can be used alone or in combination of two or more types.
[0126] The electron donor compound used for component (a) preferably contains a phthalate-based compound as an essential component. When a catalyst (X) containing a phthalate-based compound as an electron donor is used, propylene polymer M can be readily obtained. w / M n Polypropylene-based resins within the above-mentioned range.
[0127] Examples of compounds based on phthalate esters include monoethyl phthalate, dimethyl phthalate, methyl ethyl phthalate, monoisobutyl phthalate, mono-n-butyl phthalate, diethyl phthalate, ethyl isobutyl phthalate, ethyl n-butyl phthalate, di-n-propyl phthalate, diisopropyl phthalate, di-n-butyl phthalate, diisobutyl phthalate, di-n-heptyl phthalate, di-n-ethylhexyl phthalate, di-n-octyl phthalate, dinepentyl phthalate, didecyl phthalate, benzyl butyl phthalate, and diphenyl phthalate. Diisobutyl phthalate is particularly preferred.
[0128] Examples of electron donor compounds in solid catalysts, other than phthalate-based compounds, include succinate-based compounds and diether-based compounds.
[0129] Compounds based on succinates can be esters of succinic acid, or esters of succinic acid with substituents such as alkyl groups at the first or second position of succinic acid.
[0130] Specific examples include diethyl succinate, dibutyl succinate, methyl diethyl succinate, diethyl diisopropyl succinate, diallyl ethyl succinate, etc.
[0131] Examples of diether-based compounds include: 1,3-diethers, such as 2-(2-ethylhexyl)-1,3-dimethoxypropane, 2-isopropyl-1,3-dimethoxypropane, 2-butyl-1,3-dimethoxypropane, 2-sec-butyl-1,3-dimethoxypropane, 2-cyclohexyl-1,3-dimethoxypropane, 2-phenyl-1,3-dimethoxypropane, 2-tert-butyl-1,3-dimethoxypropane, 2-cumyl-1,3-dimethoxypropane, 2-(2-phenylethyl)-1,3-dimethoxypropane, 2-(2-cyclohexylethyl)-1,3-dimethoxypropane, 2-(p-chlorophenyl)-1,3-dimethoxypropane, 2-(diphenylmethyl)-1,3-dimethoxypropane, 2-( 1-Naphthyl)-1,3-dimethoxypropane, 2-(p-fluorophenyl)-1,3-dimethoxypropane, 2-(1-decahydronaphthyl)-1,3-dimethoxypropane, 2-(p-tert-butylphenyl)-1,3-dimethoxypropane, 2,2-dicyclohexyl-1,3-dimethoxypropane, 2,2-diethyl-1,3-dimethoxypropane, 2,2-dipropyl-1,3-dimethoxypropane, 2,2-dibutyl-1,3-dimethoxypropane, 2,2-diethyl-1,3-diethoxypropane, 2,2-dicyclopentyl-1,3-dimethoxypropane, 2,2-dipropyl-1,3-diethoxypropane, 2,2-dibutyl-1,3-diethoxypropane, 2-methyl-2-ethyl-1,3-di Methoxypropane, 2-methyl-2-propyl-1,3-dimethoxypropane, 2-propyl-2-pentyl-1,3-diethoxypropane, 2-methyl-2-benzyl-1,3-dimethoxypropane, 2-methyl-2-phenyl-1,3-dimethoxypropane, 2-methyl-2-cyclohexyl-1,3-dimethoxypropane, 2-methyl-2-methylcyclohexyl-1,3-dimethoxypropane, 2,2-bis(p-chlorophenyl)-1,3-dimethoxypropane, 2,2-bis(2-phenylethyl)-1,3-dimethoxypropane, 2,2-bis(2-cyclohexylethyl)-1,3-dimethoxypropane, 2-methyl-2-isobutyl-1,3-dimethoxypropane, 2-methyl-2-(2-ethylhexyl)-1... 3-Dimethoxypropane, 2,2-bis(2-ethylhexyl)-1,3-dimethoxypropane, 2,2-bis(p-methylphenyl)-1,3-dimethoxypropane, 2-methyl-2-isopropyl-1,3-dimethoxypropane, 2,2-diisobutyl-1,3-dimethoxypropane, 2,2-diphenyl-1,3-dimethoxypropane, 2,2-dibenzyl-1,3-dimethoxypropane, 2-isopropyl-2-cyclopentyl-1,3-dimethoxypropane, 2,2-bis(cyclohexylmethyl)-1,3-dimethoxypropane, 2,2-diisobutyl-1,3-diethoxypropane, 2,2-diisobutyl-1,3-dibutoxypropane, 2-isobutyl-2-isopropyl-1,3-dimethoxypropane, 2,2-Di-sec-butyl-1,3-dimethoxypropane, 2,2-di-tert-butyl-1,3-dimethoxypropane, 2,2-dineopentyl-1,3-dimethoxypropane, 2-isopropyl-2-isopentyl-1,3-dimethoxypropane, 2-phenyl-2-benzyl-1,3-dimethoxypropane, 2-cyclohexyl-2-cyclohexylmethyl-1,3-dimethoxypropane, etc.
[0132] Other specific examples of compounds based on 1,3-diethers include the following.
[0133] 1,1-bis(methoxymethyl)-cyclopentadiene; 1,1-bis(methoxymethyl)-2,3,4,5-tetramethylcyclopentadiene; 1,1-bis(methoxymethyl)-2,3,4,5-tetraphenylcyclopentadiene; 1,1-bis(methoxymethyl)-2,3,4,5-tetrafluorocyclopentadiene; 1,1-bis(methoxymethyl)-3,4-dicyclopentylcyclopentadiene; 1,1-bis(methoxymethyl)indene; 1,1-bis(methoxymethyl)-2,3-dimethylindene; 1,1-bis(methoxymethyl)-4,5,6,7-tetrahydroindene; 1,1-bis(methoxymethyl)-2,3,6,7-tetrafluoroindene; 1,1-bis(methoxymethyl) 1,1-Dimethylindene; 1,1-bis(methoxymethyl)-3,6-dimethylindene; 1,1-bis(methoxymethyl)-4-phenylindene; 1,1-bis(methoxymethyl)-4-phenyl-2-methylindene; 1,1-bis(methoxymethyl)-4-cyclohexene; 1,1-bis(methoxymethyl)-7-(3,3,3-trifluoropropyl)indene; 1,1-bis(methoxymethyl)-7-trimethylsilylindene; 1,1-bis(methoxymethyl)-7-trifluoromethylindene; 1,1-bis(methoxymethyl)-4,7-dimethyl-4,5,6,7-tetrahydroindene; 1,1-bis(methoxymethyl)-7-methylindene; 1,1-bis(methoxymethyl)-4,7-dimethyl-4,5,6,7-tetrahydroindene; 1,1-bis(methoxymethyl)-7-methylindene; 1,1-bis(methoxymethyl)-4-dimethyl-4,5,6,7-tetrahydroindene; 1,1-Bis(methoxymethyl)-7-isopropylindene; 1,1-Bis(methoxymethyl)-7-cyclohexylindene; 1,1-Bis(methoxymethyl)-7-tert-butylindene; 1,1-Bis(methoxymethyl)-7-tert-butyl-2-methylindene; 1,1-Bis(methoxymethyl)-7-phenylindene; 1,1-Bis(methoxymethyl)-2-phenylindene; 1,1-Bis(methoxymethyl)-1H-benzo[a]indene; 1,1-Bis(methoxymethyl)-1H-2-methylbenzo[a]indene; 9,9-Bis(methoxymethyl)fluorene; 9,9-Bis(methoxymethyl)-2,3,6,7-tetramethylfluorene; 9,9-Bis(methoxymethyl)- 2,3,4,5,6,7-Hexafluorofluorene; 9,9-bis(methoxymethyl)-2,3-benzo[a]fluorene; 9,9-bis(methoxymethyl)-2,3,6,7-dibenzo[a]fluorene; 9,9-bis(methoxymethyl)-2,7-diisopropylfluorene; 9,9-bis(methoxymethyl)-1,8-dichlorofluorene; 9,9-bis(methoxymethyl)-2,7-dicyclopentylfluorene; 9,9-bis(methoxymethyl)-1,8-difluorofluorene; 9,9-bis(methoxymethyl)-1,2,3,4-tetrahydrofluorene; 9,9-bis(methoxymethyl)-1,2,3,4,5,6,7,8-octahydrofluorene; 9,9-bis(methoxymethyl)-4-tert-butylfluorene.
[0134] Examples of halogen atoms constituting component (a) include fluorine, chlorine, bromine, iodine or mixtures thereof, with chlorine being particularly preferred.
[0135] Examples of organoaluminum compounds in component (b) include: trialkylaluminum, such as triethylaluminum and tributylaluminum; trienylaluminum, such as triisopentenylaluminum; alkoxydialkylaluminum, such as diethylethoxyaluminum and dibutylbutoxyaluminum; sesquialkoxyalkylaluminum, such as sesquiethoxyethylaluminum and sesquibutoxybutylaluminum, with an average composition of R. 1 2.5 Al(OR 2 ) 0.5 (R 1 and R 2 These are, respectively, partially alkoxylated alkyl aluminum groups (which may be different or the same); dialkyl aluminum halides, such as diethylaluminum chloride, dibutylaluminum chloride, and diethylaluminum bromide; alkyl sesquihalides, such as ethylaluminum sesquichloride, butylaluminum sesquichloride, and ethylaluminum sesquibromide; partially halogenated alkyl aluminum groups, such as dialkyl aluminum halides, such as ethylaluminum dichloride, propylaluminum dichloride, and butylaluminum dibromide; partially hydrogenated alkyl aluminum groups, such as hydrogenated dialkyl aluminum halides, such as diethylaluminum hydride, dibutylaluminum hydride, and dihydroalkyl aluminum halides (e.g., ethylaluminum dihydrogenate and propylaluminum dihydrogenate); and partially alkoxylated and halogenated alkyl aluminum groups, such as ethoxyethylaluminum chloride, butoxybutylaluminum chloride, and ethoxyethylaluminum bromide. Component (b) above can be used alone or in combination of two or more types.
[0136] As the external electron donor compound for component (c), an organosilicon compound is used.
[0137] Preferred organosilicon compounds include, for example, trimethylmethoxysilane, trimethylethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diisopropyldimethoxysilane, tert-butylmethyldimethoxysilane, tert-butylmethyldiethoxysilane, tert-pentylmethyldiethoxysilane, diphenyldimethoxysilane, phenylmethyldimethoxysilane, diphenyldiethoxysilane, di-o-tolyldimethoxysilane, di-m-tolyldimethoxysilane, di-p-tolyldimethoxysilane, di-p-tolyldiethoxysilane, diethylphenyldimethoxysilane, dicyclohexyldimethoxysilane, cyclohexylmethyldimethoxysilane, cyclohexylmethyldiethoxysilane, and ethyltrimethoxysilane. Ethyltriethoxysilane, Vinyltrimethoxysilane, Methyltrimethoxysilane, n-Propyltriethoxysilane, Decyltrimethoxysilane, Decyltriethoxysilane, Phenyltrimethoxysilane, γ-Chloropropyltrimethoxysilane, Methyltriethoxysilane, Vinyltriethoxysilane, Tert-Butyltriethoxysilane, Xylenetrimethoxysilane, n-Butyltriethoxysilane, Isobutyltriethoxysilane, Phenyltriethoxysilane, γ-Aminopropyltriethoxysilane, Chlorotriethoxysilane, Ethyltriisopropoxysilane, Vinyltributoxysilane, Cyclohexyltrimethoxysilane, Cyclohexyltriethoxysilane, 2-Norbornanetrimethoxysilane, 2-Norbornanetriethoxysilane, 2- Norbornene methyl dimethoxysilane, ethyl silicate, butyl silicate, trimethylphenoxysilane, methyltriallyloxysilane, vinyltris(β-methoxyethoxysilane), vinyltriacetoxysilane, dimethyltetraethoxydisiloxane, methyl(3,3,3-trifluoron-propyl)dimethoxysilane, cyclohexylethyldimethoxysilane, cyclopentyltert-butoxydimethoxysilane, diisobutyldimethoxysilane, isobutylisopropyldimethoxysilane, n-propyltrimethoxysilane, di-n-propyldimethoxysilane, tert-butylethyldimethoxysilane, tert-butylpropyldimethoxysilane, tert-butyltert-butoxydimethoxysilane, isobutyltrimethoxysilane, cyclohexylisobutyldimethoxysilane Silane, di-sec-butyldimethoxysilane, isobutylmethyldimethoxysilane, bis(decahydroisoquinoline-2-yl)dimethoxysilane, diethylaminotriethoxysilane, dicyclopentylbis(ethylamino)silane, tetraethoxysilane, tetramethoxysilane, isobutyltriethoxysilane, tert-butyltrimethoxysilane, isobutyltrimethoxysilane, isobutyl-sec-butyldimethoxysilane, ethyl(perhydroisoquinoline-2-yl)dimethoxysilane, tris(isopropenyloxy)phenylsilane, isobutylisopropyldimethoxysilane, cyclohexylisobutyldimethoxysilane, cyclopentylisobutyldimethoxysilane, cyclopentylisopropyldimethoxysilane, phenyltriethoxysilane, p-tolylmethyldimethoxysilane, etc.
[0138] Among them, the preferred formulations are ethyltriethoxysilane, n-propyltriethoxysilane, n-propyltrimethoxysilane, tert-butyltriethoxysilane, tert-butylmethyldimethoxysilane, tert-butylmethyldiethoxysilane, tert-butylethyldimethoxysilane, tert-butylpropyldimethoxysilane, tert-butyltert-butoxydimethoxysilane, tert-butyltrimethoxysilane, isobutyltrimethoxysilane, isobutylmethyldimethoxysilane, isobutylsec-butyldimethoxysilane, ethyl(perhydroisoquinoline-2-yl)dimethoxysilane, bis(decahydroisoquinoline-2-yl)dimethoxysilane, tris(isopropenoxy)phenylsilane, xylenetrimethoxysilane, vinyltriethoxysilane, phenyltriethoxysilane, phenyltrimethoxysilane, vinyltributoxysilane, diphenyldimethoxysilane, diisopropyldimethoxysilane, and diisobutyl... Dimethoxysilane, isobutylisopropyldimethoxysilane, cyclopentyltert-butoxydimethoxysilane, dicyclopentyldimethoxysilane, cyclohexylmethyldimethoxysilane, cyclohexylisobutyldimethoxysilane, cyclopentylisobutyldimethoxysilane, cyclopentylisopropyldimethoxysilane, disec-butyldimethoxysilane, diethylaminotriethoxysilane, tetraethoxysilane, tetramethoxysilane, isobutyltriethoxysilane, phenylmethyldimethoxysilane, phenyltriethoxysilane, di-p-toluenedimethoxysilane, p-toluenemethyldimethoxysilane, dicyclohexyldimethoxysilane, cyclohexylethyldimethoxysilane, 2-norbornanetriethoxysilane, 2-norbornanemethyldimethoxysilane, diphenyldiethoxysilane, methyl(3,3,3-trifluoropropyl)dimethoxysilane, ethyl silicate, etc. The above component (c) can be used alone or in combination of two or more types.
[0139] Organosilicon compounds play a particularly important role in regulating the amount of the xylene insoluble fraction. When other catalyst components are the same, the amount of the xylene insoluble fraction depends on the type and amount of the organosilicon compound and the polymerization temperature. However, even when using a suitable organosilicon compound, the amount of the xylene insoluble fraction decreases significantly when the amount of the organosilicon compound is below a certain value, typically with the exception of diether catalysts. Therefore, when the polymerization temperature is 75°C, the lower limit of the molar ratio of organosilicon compound to organoaluminum compound (organosilicon compound / organoaluminum compound) is preferably 0.015, more preferably 0.018. The upper limit of this ratio is preferably 0.30, more preferably 0.20, and even more preferably 0.10. That is, examples include the ranges of 0.015 to 0.30, 0.015 to 0.20, 0.015 to 0.10, 0.018 to 0.30, 0.018 to 0.20, and 0.018 to 0.10.
[0140] When phthalate-based compounds are used as internal electron donor compounds, the increased polymerization temperature leads to an increase in the xylene-insoluble portion, thereby lowering the lower and upper limits of the preferred molar ratio (organosilicon / organoaluminum) of the organosilicon compound and the organosilicone compound. Specifically, when using phthalate-based compounds to polymerize at 80°C, the lower limit of the molar ratio is preferably 0.010, more preferably 0.015, and even more preferably 0.018. The upper limit of the molar ratio is preferably 0.20, more preferably 0.14, and even more preferably 0.08. That is, examples include the ranges of 0.010 to 0.20, 0.010 to 0.14, 0.010 to 0.08, 0.015 to 0.20, 0.015 to 0.14, 0.015 to 0.08, 0.018 to 0.20, 0.018 to 0.14, and 0.018 to 0.08.
[0141] As catalyst (X), preferred component (b) is trialkylaluminum, such as triethylaluminum or triisobutylaluminum, and component (c) is an organosilicon compound, such as dicyclopentyldimethoxysilane, cyclohexylmethyldimethoxysilane, or diisopropyldimethoxysilane.
[0142] The method of obtaining a polymer mixture by multi-stage polymerization is not limited to the above. The propylene polymer (component (a1)) can be polymerized in multiple polymerization reactors, or the ethylene / α-olefin copolymer (component (a2)) can be polymerized in multiple polymerization reactors.
[0143] Another method for obtaining the polymer mixture is to use a polymerization vessel with a monomer concentration gradient or a polymerization condition gradient. In such a polymerization vessel, for example, a polymerization vessel in which at least two polymerization zones are connected can be used, and the monomers can be polymerized by gas-phase polymerization.
[0144] Specifically, in the presence of a catalyst, monomers are supplied and polymerized in a polymerization zone consisting of risers, and monomers are supplied and polymerized in a downcomer connected to the risers, with polymerization occurring simultaneously between the risers and downcomers, and the polymerization products are collected. The method includes means for completely or partially preventing the gas mixture present in the risers from entering the downcomers. Furthermore, a gas and / or liquid mixture having a different composition from the gas mixture present in the risers is introduced into the downcomers. For such a polymerization method, the method described in Japanese Patent Publication No. 2002-520426 can be applied, for example.
[0145] (Preparation method of ethylene / α-olefin copolymer (B))
[0146] Ethylene / α-olefin copolymers (B) can be prepared by known methods using metallocene or semi-metallocene catalysts during polymerization (e.g., as described in WO2006 / 102155). During polymerization, known auto-molecular weight modifiers, such as chain transfer agents (e.g., hydrogen or diethylzinc), can be used.
[0147] <Membrane Molding Products>
[0148] The film-molded articles of the present invention are formed by molding the polypropylene-based resin composition of the present invention. Figure 2 A roll of film molding 10 is shown as an example of the present invention.
[0149] The film-molded articles of the present invention can be prepared, for example, by a casting process. This is carried out at a molding temperature of, for example, 150 to 350°C, preferably 170 to 250°C.
[0150] The thickness of the film-molded article of the present invention can be, for example, 0.001 mm to 0.1 mm, preferably 0.01 mm to 0.09 mm, and more preferably 0.03 mm to 0.09 mm. The thickness of the film-molded article is measured using a known non-contact measurement method (such as a beta-ray film thickness gauge).
[0151] Because the film-molded articles of the present invention have excellent low-temperature impact resistance, they can be used in low-temperature environments, for example, -20 to 10°C, preferably -10 to 4°C, and more preferably -5 to 0°C.
[0152] When measured by the following test method, the membrane impact resistance of the membrane molded article of the present invention at -5°C after distillation treatment is preferably 35 kJ / m or higher, and the higher the impact resistance, the more preferred.
[0153] Since the film-molded articles of the present invention are formed from a polypropylene-based resin composition with excellent food hygiene properties, they are suitable for contact with food, especially for use as packaging or containers. Figure 3 A cup-shaped food container 20 formed from a film molding article is shown as an example of the present invention.
[0154] Regarding the membrane molded article of the present invention, the amount eluted into n-hexane in the following FDA test is preferably less than 2.6% by weight, and the smaller the amount, the better.
[0155] Because the film-molded product of the present invention has excellent adhesive strength (sealing strength after distillation) after heat sterilization in the hot-pressed weldment, it is suitable for use as a retort pouch (a food bag that needs to be heat sterilized). Figure 4A food retort pouch 30 manufactured using a film-molded article is shown as an example of the present invention. In the retort pouch 30, preferably, the film-molded article of the present invention forms the inner surface that comes into contact with the food. The retort pouch 30 can be formed using only the film-molded article of the present invention, or it can be formed from a laminated film in which other layers such as an aluminum layer are laminated. The film-molded article of the present invention can constitute any layer of the laminated film. The retort pouch 30 is also an example of food-contact packaging according to the present invention.
[0156] Regarding the membrane molded product of the present invention, the sealing strength after distillation treatment, as determined by the following test method, is preferably 50 N / 15 mm or higher, and the higher the sealing strength, the more preferred.
[0157] The tensile modulus of the film-molded article of the present invention is preferably 400 MPa or more in the MD and TD directions, and a higher tensile modulus is more preferred. Here, the tensile modulus is a value measured by the following test method.
[0158] The higher the tensile modulus, the better the rigidity of the molded film, and the more suitable it is for use as packaging or containers for storing solid substances inside.
[0159] [Example of an embodiment]
[0160] Examples and comparative examples are shown below, but the invention is not limited to the following examples.
[0161] <Preparation of Copolymer 1>
[0162] A solid catalyst in which TiCl4 and diisobutyl phthalate are supported on MgCl2 as internal donors is prepared by the method described in Example 5 of European Patent No. 728769, lines 46 to 53. Specifically, it is carried out as follows.
[0163] Microprolate MgCl2·2·1C2H5OH was prepared as follows. In a 2L autoclave equipped with a turbine stirrer and pipette, 48g of anhydrous MgCl2, 77g of anhydrous C2H5OH, and 830mL of kerosene were placed in an inert gas atmosphere at room temperature. The contents were heated to 120°C with stirring to obtain an adduct of MgCl2 and alcohol, which was melted and mixed with a dispersant. The nitrogen pressure inside the autoclave was maintained at 15 atm. The pipette of the autoclave was heated to 120°C using a heating jacket. The pipette had an inner diameter of 1mm and a length of 3m from one end of the heating jacket to the other. The mixture flowed through the pipette at a rate of 7m / s. At the outlet of the pipette, the dispersion was collected with stirring into a 5L flask containing 2.5L of kerosene and cooled externally with a jacket maintained at an initial temperature of -40°C. The final temperature of the dispersion was 0°C. The spherical solid product constituting the emulsion dispersion was allowed to settle, separated by filtration, washed with heptane, and dried. All these operations were carried out under an inert gas atmosphere. MgCl₂·3C₂H₅OH in the form of solid spherical particles with a maximum diameter of 50 μm or less was obtained. The yield was 130 g. An alcohol-free product was obtained by gradually increasing the temperature from 50 °C to 100 °C in a nitrogen stream until the alcohol content per mole of MgCl₂ decreased to 2.1 mol.
[0164] 225 mL of TiCl4 was added to a 500 mL cylindrical glass reactor equipped with a filter barrier at 0 °C, and 10.1 g (54 mmol) of the microspheres MgCl2·2·1C2H5OH obtained above was added while stirring the contents for 15 minutes. The temperature was then raised to 40 °C and 9 mmol of diisobutyl phthalate was added. The temperature was raised to 100 °C over 1 hour and stirring continued for another 2 hours. TiCl4 was then removed by filtration, and another 200 mL of TiCl4 was added for 1 hour while stirring at 120 °C. Finally, the contents were filtered and washed with n-heptane at 60 °C until the filtrate was completely free of chloride ions. The resulting catalyst composition contained 3.3 wt% Ti and 8.2 wt% diisobutyl phthalate.
[0165] Then, the solid catalyst described above, triethylaluminum (TEAL) as an organoaluminum compound, and dicyclopentyldimethoxysilane (DCPMS) as an external electron donor compound were contacted at 12°C for 24 minutes, with the amounts such that the weight ratio of TEAL to the solid catalyst was 20 and the weight ratio of TEAL / DCPMS was 10 (0.05 when converted to the above organosilicon compound / organoaluminum molar ratio).
[0166] Prepolymerization was performed by keeping the obtained catalyst (X) in suspension in liquid propylene at 20°C for 5 minutes.
[0167] The obtained prepolymerized product is introduced into the first-stage polymerization reactor of a polymerization apparatus equipped with two-stage polymerization reactors connected in series, and propylene is supplied to prepare a propylene homopolymer. Subsequently, the propylene homopolymer, propylene, and ethylene are supplied to the second-stage polymerization reactor to produce an ethylene / propylene copolymer. During polymerization, temperature and pressure are regulated, and hydrogen is used as a molecular weight regulator.
[0168] The polymerization temperature and reactant ratios were as follows: in the first reactor, the polymerization temperature and hydrogen concentration were 80°C and 0.12 mol%, respectively; and in the second reactor, the polymerization temperature, hydrogen concentration, and the ratio of ethylene to the total amount of ethylene and propylene were 80°C, 1.33 mol%, and 0.25 molar ratio, respectively. Furthermore, the residence time distribution of the first and second stages was adjusted so that the amount of the ethylene / propylene copolymer was 32% by weight. The target copolymer 1 was obtained using the above method.
[0169] The obtained copolymer 1 is a polymeric mixture of component (a1) and component (a2), component (a1) being a propylene polymer constituting the continuous phase and component (a2) being an ethylene / propylene copolymer constituting the rubber phase, and is a polypropylene-based resin (A).
[0170] For copolymer 1, the molecular weight distribution Mw / Mn of component (a1), the content of ethylene-derived units of component (a1), the weight ratio of component (a2) / [component (a1) + component (a2)], the content of ethylene-derived units of component (a2), the XSIV of component (a1) + component (a2), and the MFR of component (a1) + component (a2) are shown in Table 1.
[0171] In Table 1, catalysts (X) containing phthalate-based compounds as component (a) are denoted as "Pht", and catalysts (X) containing succinate-based compounds as component (a) are denoted as "Suc".
[0172] The catalyst (X) obtained by the above method is denoted as "Pht-1" in Table 1.
[0173] <Preparation of copolymers 2 to 4>
[0174] The residence times in the first and second stages were adjusted so that the weight ratio of component (a2) / [component (a1) + component (a2)] was as shown in Table 1. In addition to changing the distribution, the hydrogen concentration in the first stage was adjusted to regulate the MFR of component (a1) + component (a2). Regarding copolymer 3, the ratio of ethylene to the total amount of ethylene and propylene in the second reactor was changed so that the content of ethylene-derived units in component (a2) was as shown in Table 1. Otherwise, copolymers 2 to 4 were obtained using the same manufacturing method as for copolymer 1.
[0175] <Preparation of copolymer 5>
[0176] A solid catalyst in which Ti and diisobutyl phthalate are supported on MgCl2 as internal donors is prepared by the method described in paragraph 0032, lines 21 to 36 of JP-A-2004-27218. Specifically, the preparation is as follows.
[0177] Under a nitrogen atmosphere at 120°C, 56.8 g of anhydrous magnesium chloride was completely dissolved in 100 g of anhydrous ethanol, 500 mL of petroleum jelly oil "CP15N" manufactured by Idemitsu Kosan Co., Ltd., and 500 mL of silicone oil "KF96" manufactured by Shin-Etsu Silicone Co., Ltd. The solution was stirred for 2 minutes at 120°C and 5000 rpm using a TK homogenizer manufactured by Tokushu Kika Kogyo Co., Ltd. While stirring, it was poured into 2 L of anhydrous heptane, with the temperature not exceeding 0°C. The resulting white solid was thoroughly washed with anhydrous heptane, dried under vacuum at room temperature, and further partially deethanolinated under a nitrogen atmosphere to obtain 30 g of spherical solid MgCl2·1.2C2H5OH.
[0178] 30 g of the above spherical solid was suspended in 200 mL of anhydrous heptane. While stirring at 0 °C, 500 mL of titanium tetrachloride was added dropwise over 1 hour. Next, when heating began and the temperature reached 40 °C, 4.96 g of diisobutyl phthalate was added, and the temperature was raised to 100 °C over approximately 1 hour. After reacting at 100 °C for 2 hours, the solid fraction was collected by hot filtration. Subsequently, 500 mL of titanium tetrachloride was added to the reaction mixture and stirred, followed by reaction at 120 °C for 1 hour. After the reaction was complete, the solid fraction was again collected by hot filtration, washed seven times with 1.0 L of hexane at 60 °C and three times with 1.0 L of hexane at room temperature to obtain the solid catalyst. The titanium content in the obtained solid catalyst fraction was measured and found to be 2.36% by weight.
[0179] In addition to using the aforementioned solid catalyst, copolymer 5, as shown in Table 1, was obtained by the same manufacturing method as copolymer 1. However, the hydrogen concentration in the first-stage reactor was changed to 0.11 mol%, and the residence time distribution in the second stage was also adjusted so that the weight ratio of component (a2) / [component (a1) + component (a2)] was 28 wt%.
[0180] The catalyst (X) obtained by the above method after contact with TEAL and DCPMS is denoted as "Pht-2" in Table 1.
[0181] <Preparation of copolymer 6>
[0182] The hydrogen concentration and the ratio of ethylene to the sum of ethylene and propylene in the second-stage reactor were changed so that the XSIV of component (a1) + component (a2) and the ethylene-derived unit content of component (a2) were the values listed in Table 1. Additionally, the residence time distribution of the first and second stages was changed so that the weight of component (a2) / [component (a1) + component (a2)] was as shown in Table 1, and the hydrogen concentration in the first stage was adjusted to change the MFR of component (a1) + component (a2) to the values shown in Table 1. Apart from the above, copolymer 6 was obtained using the same manufacturing method as copolymer 5.
[0183] <Preparation of copolymers 7 and 8>
[0184] The ratio of ethylene to the total amount of ethylene and propylene in the second-stage reactor was adjusted so that the content of ethylene-derived units in component (a2) was as shown in Table 1. Apart from the above adjustments, copolymers 7 to 8 were obtained in the same manner as copolymer 1.
[0185] <Preparation of copolymers 9 and 10>
[0186] The hydrogen concentration in the second-stage reactor was changed so that the XSIV of component (a1) + component (a2) was the value listed in Table 1, and the hydrogen concentration in the first stage was also adjusted to adjust the MFR of component (a1) + component (a2). Apart from the above, copolymers 9 and 10 were obtained in the same manner as copolymer 1.
[0187] <Preparation of copolymers 11 and 12>
[0188] The hydrogen concentration in the first stage was adjusted so that the MFR of component (a1) + component (a2) was the value listed in Table 1. Apart from the above, copolymers 11 and 12 were obtained using the same manufacturing method as copolymer 1.
[0189] <Preparation of copolymer 13>
[0190] A solid catalyst was prepared using the following procedure, based on the preparation method described in the example of Japanese Patent Application Publication No. 2011-500907.
[0191] At 0 °C, 250 mL of TiCl4 was introduced into a 500 mL four-necked round-bottom flask purged with nitrogen. With stirring, 10.0 g of microspheres of MgCl2·1.8C2H5OH (prepared according to the method described in Example 2 of USP-4,399,054, but operated at 3000 rpm instead of 10000 rpm) and 9.1 mmol of diethyl succinate-2,3-(diisopropyl) ester were added. The temperature was raised to 100 °C and maintained for 120 min. Afterward, stirring was stopped, the solid product was allowed to settle, and the supernatant was aspirated. The following procedure was then repeated twice: 250 mL of fresh TiCl4 was added, the mixture was reacted at 120 °C for 60 min, and the supernatant was aspirated. The solid was washed six times at 60 °C with anhydrous hexane (6 x 100 mL).
[0192] The solid catalyst, TEAL, and DCPMS were brought into contact with each other at room temperature for 5 minutes with a TEAL to solid catalyst weight ratio of 18 and a TEAL / DCPMS weight ratio of 10. Prepolymerization was then carried out by keeping the obtained catalyst (X) in suspension in liquid propylene at 20°C for 5 minutes.
[0193] The obtained prepolymerized product is introduced into the first-stage polymerization reactor of a polymerization apparatus equipped with two-stage polymerization reactors connected in series, and propylene is supplied to prepare a propylene homopolymer. Subsequently, the propylene homopolymer, propylene, and ethylene are supplied to the second-stage polymerization reactor to produce an ethylene / propylene copolymer. During polymerization, temperature and pressure are regulated, and hydrogen is used as a molecular weight regulator.
[0194] The polymerization temperature and reactant ratios were as follows: in the first reactor, the polymerization temperature and hydrogen concentration were 80°C and 0.14 mol%, respectively; and in the second reactor, the polymerization temperature, hydrogen concentration, and the ratio of ethylene to the total amount of ethylene and propylene were 80°C, 1.33 mol%, and 0.25 molar ratio, respectively. Furthermore, the residence time distribution of the first and second stages was adjusted so that the amount of the ethylene / propylene copolymer was 32% by weight. The target copolymer 13 was obtained using the above method.
[0195] Regarding copolymer 13, the molecular weight distribution Mw / Mn of component (a1), the content of ethylene-derived units of component (a1), the weight ratio of component (a2) / [component (a1) + component (a2)], the content of ethylene-derived units of component (a2), the XSIV of component (a1) + component (a2), and the MFR of component (a1) + component (a2) are shown in Table 1.
[0196] Copolymers 2 to 13 obtained above were measured in the same manner as copolymer 1, and the results are shown in Table 1.
[0197] [Table 1]
[0198]
[0199] The measurements in Table 1 were taken using the following methods.
[0200] <Mw / Mn of component (a1)>
[0201] A 2.5g sample of component (a1) polymerized in the first-stage reactor was used as a measurement sample, and the number-average molecular weight (Mn) and weight-average molecular weight (Mw) were measured. The weight-average molecular weight (Mw) was divided by the number-average molecular weight (Mn) to determine the molecular weight distribution (Mw / Mn).
[0202] The equipment used was a PL GPC220 manufactured by Polymer Laboratories. The mobile phase was 1,2,4-trichlorobenzene containing antioxidants, and the columns were UT-G (one column), UT-807 (one column), and UT-806M (two columns) connected in series, manufactured by Showa Denko. A differential refractometer was used as the detector. The same solvent as the mobile phase was used as the solvent for the sample solution, and a measurement sample with a concentration of 1 mg / mL was prepared by dissolving the sample at 150°C with stirring for 2 hours. 500 μL of the resulting sample solution was injected into the column, and measurements were taken at a flow rate of 1.0 mL / min, a temperature of 145°C, and a data collection interval of 1 second. The columns were calibrated using a triple approximation method with polystyrene standard samples (Shodex STANDARD, manufactured by Showa Denko) with molecular weights ranging from 5.8 million to 7.45 million. K = 1.21 × 10⁻⁶ for using polystyrene standard samples. -4 α = 0.707 and K = 1.37 × 10 for polypropylene homopolymer, propylene random copolymer and polypropylene-based polymer. -4 And the Mark-Houwink-Sakurada coefficient with α = 0.75.
[0203] <Total ethylene content of the copolymer, content of ethylene-derived units in component (a1)>
[0204] For copolymer samples dissolved in a mixed solvent of 1,2,4-trichlorobenzene / deuterated benzene, AVANCE III HD400 manufactured by Bruker was used. 13 The C-resonance frequency (100MHz) is obtained under the following conditions. 13 C-NMR spectroscopy: measurement temperature 120℃, flip angle 45 degrees, pulse interval 7 seconds, sample rotation speed 20Hz, integration times 5000.
[0205] Using the spectra obtained above, the total ethylene content (wt%) of the copolymer was determined by the method described by Kakugo, Y. Naito, K. Mizunuma and T. Miyatake in Macromolecules 15, 1150-1152 (1982).
[0206] In addition, when measuring component (a1) as a sample, the total ethylene content (wt%) obtained by the above method is the ethylene unit content (wt%) of component (a1).
[0207] <Ethylene unit content in component (a2)>
[0208] The ethylene unit content (wt%) of component (a2) was determined by calculation in the same manner as the total ethylene content, except that the integral intensity Tββ obtained when measuring the total ethylene content of the copolymer was no longer used in the method described in the above literature, but the integral intensity T'ββ obtained by the following formula was used instead.
[0209] T'ββ=0.98×Sαγ×A / (1-0.98×A)
[0210] Here, A = Sαγ / (Sαγ+Sαδ), which is calculated from Sαγ and Sαδ as described in the above literature.
[0211] <weight ratio of component (a2) / [weight ratio of component (a1) + component (a2)]>
[0212] It is determined by the following formula.
[0213] Component (a2) / [Component (a1) + Component (a2)] (unit: weight %) = Total ethylene content of the copolymer / (Ethylene unit content in component (a2) / 100)
[0214] <XSIV of component (a1) + component (a2)>
[0215] The xylene-soluble portion of the copolymer was obtained by the following method, and the intrinsic viscosity (XSIV) of the xylene-soluble portion was measured.
[0216] 2.5 g of the copolymer sample was placed in a flask containing 250 mL of o-xylene (solvent) and stirred at 135 °C for 30 minutes using a hot plate and reflux apparatus, while purging with nitrogen to ensure complete dissolution. The solution was then cooled at 25 °C for 1 hour. The resulting solution was filtered through filter paper. 100 mL of the filtrate was collected and transferred to an aluminum cup, etc., and evaporated to dryness at 140 °C while purging with nitrogen. The evaporated solution was then allowed to stand at room temperature for 30 minutes to obtain the xylene-soluble fraction.
[0217] The intrinsic viscosity of tetrahydronaphthalene was measured at 135°C using an automated capillary viscometer (SS-780-H1, manufactured by Shibayama Scientific Instruments Co., Ltd.).
[0218] MFR of component (a1) + component (a2)
[0219] According to JIS K7210-1, 0.05 g of H-BHT manufactured by Honshu Chemical Industry Co., Ltd. was added to 5 g of copolymer sample, and the mixture was measured according to JIS K6921-2 after dry mixing and homogenization at a temperature of 230°C and a load of 2.16 kg.
[0220] [Examples and Comparisons]
[0221] According to the composition shown in Table 2, blending components (A) to (B) were performed, with 0.2 parts by weight of B225 manufactured by BASF added as an antioxidant, and 0.05 parts by weight of calcium stearate manufactured by Tannan Kagaku Kogyo Co., Ltd. added as a neutralizing agent to a total of 100 parts by weight of components (A) to (B). The mixture was stirred and mixed for 1 minute using a Henschel mixer. The mixture was melt-kneaded and extruded using a co-rotating twin-screw extruder TEX-30α manufactured by JSW at a barrel temperature of 230°C. After cooling the filament in water, the filament was cut using a granulator to obtain granules of the polypropylene-based resin composition. Various physical properties of the polypropylene-based resin composition thus prepared and the film molded articles obtained using it were evaluated. The results are shown in Table 2.
[0222] [Table 2]
[0223]
[0224] The components in Table 2 are as follows.
[0225] Component (A) is copolymers 1 to 13 in Table 1.
[0226] Component (B) is the following ethylene / α-olefin copolymer.
[0227] B-1: Mitsui Chemicals, Tafmer A4085, ethylene / butene copolymer, MFR (190°C, 2.16 kg) = 3.6 g / 10 minutes
[0228] Other ingredients are the following additives.
[0229] Antioxidant: B225 manufactured by BASF SE
[0230] Neutralizing agent: Calcium stearate manufactured by Tannan Chemical Industry Co.,Ltd.
[0231] The measurement results and evaluation results in Table 2 are values measured and evaluated by the following methods.
[0232] <PP Plant Productivity>
[0233] The ease of preparing component (A) using the above method is evaluated according to the following four grades.
[0234] "◎": Excellent = Manufactured without any problems.
[0235] "〇": Good = Manufactured without issues.
[0236] "△": Fair = Barely producible, but the output and fluff (powder) performance are slightly inferior.
[0237] "×": Unacceptable = Problems occur during the production process, and production cannot be completed.
[0238] <Fluidity MFR>
[0239] The MFR of the polypropylene-based resin composition is measured at a temperature of 230°C and a load of 2.16kg in accordance with JIS K7210-1 and based on JIS K6921-2.
[0240] The MFR of the ethylene / α-olefin copolymer is measured at a temperature of 190°C and a load of 2.16kg based on JIS K6922-2.
[0241] <Film Molded Article>
[0242] Using a Type 3, 3-layer film / sheet molding apparatus manufactured by Thermoplastics Industries Co.,Ltd., the temperature from the cylinder to the die is controlled at 250°C, the molten resin extruded from the die using pellets as the raw material is taken out, and cooled and solidified by a cooling roll at a molding speed of 5.6 m / min to obtain a film with a thickness of 60 μm.
[0243] In Example 4, the film is formed using a raw material obtained by dry-blending component (B) into component (A) as the main raw material.
[0244] The formed film is aged at 40°C for 24 hours or more, and further conditioned in a constant temperature chamber at 23°C for 1 hour or more, and then used as a sample.
[0245] <Tensile Rigidity Modulus>
[0246] In accordance with JIS K7161, a sample cut from a film specimen was stretched at a tensile speed of 5 mm / min using Tensilon (Autocom) from T.S.E., and the tensile modulus was determined as a value obtained by dividing the load at 2% of the tangent elongation subtracted from the 0 point of the stress-strain curve by the cross-sectional area of the sample. The tensile modulus of each film specimen was measured in the MD direction and the TD direction.
[0247] <Distillation Treatment>
[0248] The film specimen was placed in a high-temperature high-pressure retort sterilizer (RCS-40RTG-FAM) manufactured by Hisaka Seisakusho, heat-sterilized at 135°C for 30 minutes using the hot water replacement method, cooled with cold water, and then taken out of the apparatus. Thus, a film specimen subjected to distillation treatment (high-temperature high-pressure sterilization) was obtained.
[0249] <Film Impact Resistance>
[0250] The pendulum impact resistance test for plastic films was carried out in accordance with ASTM-D3420. Specifically, in an atmosphere at -5°C, the impact strength of a film specimen with a width of 100 mm (along the TD direction) was measured using an impact tester equipped with a constant temperature chamber (manufactured by Toyo Seiki Seisakusho Co., Ltd.). The measured value was divided by the thickness of the sample to calculate the film impact strength (unit: kJ / m). The larger the calculated value, the better the low-temperature impact resistance. The specimens before and after the aforementioned distillation treatment were measured.
[0251] <FDA Test>
[0252] To test the amount of components eluted (elution amount) from the film specimens (those not yet subjected to distillation treatment), the n-hexane elution amount was tested (test method: §177.1520(d)(3)(ii), compliance number: §177.1520(c)3.2a).
[0253] In addition, when the use of the film involves distillation treatment, the current FDA standards require the elution amount to be less than 2.6% by weight.
[0254] <Seal Strength>
[0255] Based on JIS Z0238, the sealing strength of samples obtained through heat-sealing film was tested. First, two film samples (those not subjected to distillation treatment) were placed with their surfaces facing each other, and a commercially available PET / CPP dry laminate (80 μm thick) was laminated as a backing material onto the back of each film sample. Then, as... Figure 1 As shown, the laminate material was sandwiched between a pair of aluminum sealing strips that had been adjusted to a predetermined temperature using a heat-sealing tester (manufactured by Tester Sangyo Co., Ltd., Japan), and a gauge pressure of 0.2 MPa was applied for 1 second, followed by hot-press bonding at 170°C. The removed sample was then rapidly cooled with ice water to obtain a sample where only the portion of the sealing strips that was heat-welded was sealed. This sample was cut into 15 mm widths and subjected to the aforementioned distillation treatment. Using an Autocom (manufactured by TSE), a pair of membrane flaps were pulled in opposite directions after sealing (pulling speed: 300 mm / min), and the strength of peeling or breaking at the seal location (unit: N / 15 mm) was measured and defined as the seal strength.
[0256] <Anti-whitening properties>
[0257] When a membrane sample (not distilled) cut into 10cm squares is folded in half and unfolded, the degree of whitening of the fold mark is evaluated using the following 4-level criteria.
[0258] "◎": Excellent: No whitening occurred.
[0259] “〇”: Good: A very slight whitening was observed.
[0260] "△": It's acceptable: It appears whitish, but the degree of whitishness is relatively weak.
[0261] "×": Unacceptable: Deep whitening and distorted markings are clearly visible.
[0262] <Fish Eye (FE)>
[0263] The dimensions appearing per standard area of the measured membrane sample (undistilled) are 0.1 to... The number of FEs is assessed and evaluated according to the following four levels.
[0264] "◎": Excellent: 10 / m 2 or below
[0265] "〇": Good: 11 to 20 / m 2
[0266] "△": Acceptable: 21 to 30 / m 2
[0267] "×": Unacceptable: 31 / m2 or above
[0268] <Membrane Formability>
[0269] The films obtained by the above molding method are evaluated according to the following three levels.
[0270] "〇": Good: A high-quality product with no problems in shape, thickness, etc.
[0271] "△": Acceptable: Some defective products were found.
[0272] "×": Unacceptable: No quality product was obtained.
[0273] <Membrane Productivity>
[0274] When performing the above-mentioned membrane forming while suppressing the occurrence of FE, the degree of membrane productivity caused by the reduction in production rate is evaluated at the following three levels.
[0275] “〇”: Good: No problems and easy to produce.
[0276] "△": Acceptable: Molding can be performed if special equipment, such as polymer filters, is used, but the production rate will be reduced.
[0277] "×": Not allowed: Production rate is significantly reduced and it is difficult to produce membranes.
[0278] "Effect"
[0279] Since the membranes of Examples 1 to 4 use polypropylene-based resin compositions with predetermined physical properties, they meet the standards in various evaluations, including rigidity, low-temperature impact resistance, amount eluted into n-hexane in FDA testing, sealing strength, resistance to flexural whitening, number of fish eyes, membrane formability, and membrane productivity.
[0280] To meet the standards for food contact with the membrane, the inventors carefully studied the formulation of the entire composition. Specifically, to reduce the amount of n-hexane eluted in FDA testing, the content of ethylene-derived units in component (a2) must be kept low, which leads to poor mechanical properties. For example, because the content of ethylene-derived units in component (a2) affects the rubber properties of the composition, impact resistance at low temperatures tends to decrease. Therefore, by carefully adjusting other parameters, such as the molecular weight distribution of component (a1), the content of component (a2), and the XSIV value and MFR of component (a1) + component (a2), the present invention achieves a high balance of other mechanical properties while meeting the requirements of FDA testing standards (less than 2.6% by weight).
[0281] In Comparative Example 1, the content of component (a2) in component (A) is relatively low, and the low-temperature impact resistance after distillation treatment is poor.
[0282] In Comparative Example 2, although component (a2) had a higher content of ethylene-derived units than component (a2) in component (A), its low-temperature shock resistance after distillation was not inferior. However, it exhibited poor resistance to whitening, a high amount of FE generated, and poor membrane productivity.
[0283] In Comparative Example 3, the content of ethylene-derived units in component (a2) is low, and it can hardly produce component (A), but it suffers from poor yield and poor fluff properties. In addition, Comparative Example 3 exhibits poor low-temperature shock resistance after distillation treatment.
[0284] Comparative Example 4, which has a high content of ethylene-derived units in component (a2), elutes significantly into n-hexane during FDA testing and exhibits poor resistance to whitening.
[0285] Compared with Example 5, the XSIV of component (a1) + component (a2) is smaller, the low-temperature impact resistance after distillation is poorer, and the sealing strength after distillation is also poorer.
[0286] In Comparative Example 6, the XSIV of component (a1) + component (a2) was higher, the number of generated FEs was higher, and the membrane productivity was lower.
[0287] Comparative Example 7 could hardly produce component (A), but suffered from low yield. Furthermore, in Comparative Example 7, the flowability of component (a1) + component (a2) and the flowability of the resin composition were low, resulting in poor film formability and film productivity.
[0288] In Comparative Example 8, the flowability (MFR) of component (a1) + component (a2) is higher than that of other components, due to the higher MFR of component (a1). It is common knowledge in those skilled in the art that MFR is negatively correlated with Mw; therefore, if the Mw of component (a1) is low (higher impact resistance is better), the low-temperature impact resistance after cooking is poor. Furthermore, it is common knowledge in those skilled in the art that MFR is inversely proportional to melt viscosity. Due to the low melt viscosity of component (a1) and the relatively high melt viscosity ratio of component (a2) to component (a1), the presence of FE is relatively high compared to the XSIV of component (a1) + component (a2) due to the poor dispersion of component (a2). In addition, the insufficient melt viscosity of component (a1) + component (a2) and the insufficient melt viscosity of the resin composition result in poor film formability (film-forming properties) and reduced film productivity to obtain films with less FE.
[0289] In comparative example 9, the M of component (a1) w / M n It has a relatively large size and poor resistance to whitening and low-temperature impact after distillation.
Claims
1. A polypropylene-based resin composition, comprising: A polypropylene-based resin (A) comprising a continuous phase composed of a propylene polymer (a1) and a rubber phase composed of a copolymer of ethylene and an α-olefin having 3 to 10 carbon atoms (a2), and Ethylene / α-olefin copolymer (B), which is a copolymer of ethylene and an α-olefin having 3 to 10 carbon atoms as an optional component. The content of the polypropylene-based resin (A) is 90% by weight or more and less than 100% by weight relative to the total weight of the polypropylene-based resin composition. The content of the ethylene / α-olefin copolymer (B) is 0 to 10% by weight relative to the total weight of (A) and (B). The MFR of the polypropylene-based resin composition at 230°C and a load of 2.16 kg is 0.5 to 4.0 g / 10 min. The weight-average molecular weight M of the propylene polymer (a1) w Number-average molecular weight M n The ratio (M) w / M n Less than 7, The content of ethylene-derived units in the propylene polymer (a1) is 0.5% by weight or less relative to the total weight of the propylene polymer (a1). The content of the copolymer (a2) is 30% to 43% by weight relative to the total weight of the polypropylene-based resin (A). The content of ethylene-derived units in the copolymer (a2) is 25% to 40% by weight relative to the total weight of the copolymer (a2). The xylene-soluble portion of the polypropylene-based resin (A) has an intrinsic viscosity of 2.5 to 3.5 dl / g in tetrahydronaphthalene at 135°C, and The MFR of the polypropylene-based resin (A) at a temperature of 230°C and a load of 2.16 kg is 0.5 to 4.0 g / 10 min; in, The film molded article formed from the polypropylene-based resin composition has a hexane elution amount of less than 2.6 wt% as determined by FDA test method §177.1520(d)(3)(ii).
2. The polypropylene-based resin composition according to claim 1, wherein the propylene polymer (a1) and the copolymer (a2) are mixed by polymerization, and the polypropylene-based resin (A) is a polymeric mixture prepared by using a catalyst containing the following components (a) to (c); (a) A solid catalyst containing magnesium, titanium, halogens, and phthalate-based compounds as electron donors. (b) Organoaluminum compounds, and (c) Organosilicon compounds that act as external electron donors.
3. A method for preparing the polypropylene-based resin composition according to claim 1, comprising the following steps: In the presence of the propylene polymer (a1), an ethylene monomer and an α-olefin monomer having 3 to 10 carbon atoms are polymerized using a catalyst containing the following components (a) to (c) to obtain the polypropylene-based resin (A). (a) A solid catalyst containing magnesium, titanium, halogens, and phthalate-based compounds as electron donors as essential components. (b) Organoaluminum compounds, and (c) Organosilicon compounds that act as external electron donors.
4. A film-molded article formed from the polypropylene-based resin composition according to claim 1.
5. The film-molded article according to claim 4, which is used as packaging or container in contact with food.
6. The film-molded article according to claim 4, which is used as at least a portion of a retort pouch.
7. A food-contact packaging formed from a film-molded article according to claim 4.
8. A container for contact with food, formed from a film-molded article according to claim 4.
9. A retort pouch formed from a film-molded article according to claim 4.
Citation Information
Patent Citations
Components and catalysts for the polymerization of olefins
EP0728769A1
Method and apparatus for gas phase polymerization
JP2002520426A
Film comprising polypropylene resin composition
JP2004027218A
Method for producing highly fluid propylene polymer
JP2011500907A
Polarizer protective film, polarizing plate, and image display device
JP2021105706A
